A Cruzada versus O Juvenil : tensões entre católicos e espíritas em Sergipe (1930-1951) - Matos, Márcio Gomes de Santana (2017)
This work presents since from the begining of the press in Europe till its arrival and usage in Brazil, and one of its aim is analyse the religious journals. Those journals presented the symbolic game of dominations, struggles, disputes, conquers and doctrine manifestations, mainly produced by catholic people, because they were the main diffusers of the so called "good press", but the spiritists and the evangelicals also did use of this kind of press. It´s exposed cases of fights between catholics and spiritis, as well as how the Catholic Church behaved in front of others creeds and faiths, such as evangelicals, and the afro-brazilian religions and its ideologies and philosophies. The historical approach comes from the XIX and XX centuries on works that did a similar approach on so many religious journals spread on brazilian territory till be able to stablish a local and historical contextualization that focus on what is the role of a catholic journal (The Cruzade) and another one that is spiritist (Spiritist Youth) in Aracaju Sergipe. These two journals kept close correspondences with other journals and magazines with the same religious points of view to keep themselves stronges e tied up to the aim of to maintain their followers, in this case, the catholic ones, or the maintanance of the new followers in the case of the spiritists.